PENELITIAN TINDAKAN KELAS UNTUK MENINGKATKAN KETERAMPILAN PEMBUATAN PROPORSAL PENELITIAN MAHASISWA - Gayatri, Gayatri .; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
The aims of classroom action research are to improve students' skills in making a research proposal. Data were collected through observation and documentation. This study used qualitative descriptive analysis by using Kemmis and Taggart model. Kemmis and Taggart model carried out through four stages such as: planning, implementation, observation and reflection. The Results of this research finding that there has been increased student skills in making a research proposal. The student awareness is to improve research proposal before the presentation. The use of time and materials of presentation are become better than before.
Keywords: research proposal, Kemmis and Taggart model